Capacidad de lanzamiento en balonmano en función del puesto específico - Rivilla-Garcia, J.; Navarro Valdivielso, F.; Grande Rodriguez, I.; Sampedro Molinuevo, J. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2012)
The purpose of this study was to examine the effect of different strength methods combined with technical-tactical training on muscle power and throwing velocity in both arms of team handball players. Eleven senior players participated (25±3 years; 188,7±4,7 cm; 90,6 ±10 Kg) in this study. The season was divided into three training periods, each of eight week, to test different methods of strength training. The results show that strength training based on the contrast static - dynamic combined with technical- tactical training during the competitive season is more effective (p=0.033) that only the realization of maximum strength training combined with peak power for improving throwing velocity.